Studi Molekul Kitosan Sebagai Membran Penghantar Proton (H) Dengan Metode Ab Initio - Arif Ari Wibowo; Rahmat Gunawan; Saibun Sitorus (JURNAL KIMIA MULAWARMAN, 2019)
The aim of this research to know chitosan compound able to replace nafion performance as a conductor of proton (H+). The assessment process and computational chemistry calculations done using ab initio methods. The analysis showed chitosan energy is -1384.7601 eH and chitosan energy after bringing proton (H +) decreased respectively by -1385.2275 eH, -1385.8487 eH, -1386.3393 eH, -1386.9652 eH, -1387.4508 eH. The result obtained proved of chitosan becomes stable so that it can be used as a proton conductor.